Simple Yet Effective. Remarks on Finnish Approach to Design Promotion - Wiśnicka, Anna (Załącznik Kulturoznawczy, 2019)
This paper gathers and analyses the main parts of the Finnish model of design promotion. It starts with providing the clear idea of division into global and national mechanisms as well as into commercial and cultural initiatives. Global mechanisms work on an international level, raising the design awareness and building the global perception of Finland as the country of design. They include works of the International Council of Societies of Industrial Design (now the World Design Organisation) and UNESCO. The promotional efforts taken on the national level focus on establishing the position of the designer and raising the understanding of the importance of design in public spaces. Those are supported by national organisations such as the Arts Promotion Centre Finland (Taike), the Finnish Association for Designers (ORNAMO) and Design Forum Finland (the official organisation of the Finnish Society of Crafts and Design), as well as local initiatives. The last section looks at the role of commercial initiatives, such as fares and marketing strategies, applied to design and the importance of cultural projects, such as museum exhibitions, publications, lectures, etc. All of the measures amalgamate to form a well-established model of design promotion which has been proven to work on many levels.